Porous carbon support and method for producing the same, silicon-carbon composite material and method for producing the same, and battery

CN121709619BActive Publication Date: 2026-10-27LENOVO (BEIJING) LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511958182.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-23
Publication Date
2026-10-27
Estimated Expiration
2045-12-23

AI Technical Summary

Technical Problem

相关技术中,锂离子电池的负极材料多使用碳材料,并通过化学活化的方式来尝试增加孔隙率,但是化学活化会对碳材料的骨架结构破坏严重,不仅影响造孔效果,还会降低碳材料的机械强度,进而影响电化学性能

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121709619B_ABST
    Figure CN121709619B_ABST
Patent Text Reader

Abstract

The present disclosure provides a porous carbon carrier and a preparation method thereof, a silicon-carbon composite material and a preparation method thereof, and a battery, and belongs to the technical field of battery materials. The porous carbon material comprises: a carbon base, the carbon base comprises a pore structure, and the carbon base is loaded with nanofibers; the pore structure is obtained by pore making using a two-dimensional template agent, the two-dimensional template agent is a two-dimensional metal hydroxide, and the nanofibers are obtained by cross-linking nanocellulose and metal ions in a metal salt cross-linking agent. The present disclosure also provides a battery comprising the porous carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to the field of battery materials technology, and in particular to a porous carbon support and its preparation method, a silicon-carbon composite material and its preparation method, and a battery. Background Technology

[0002] Lithium-ion batteries are important energy storage devices, and their performance mainly depends on the characteristics of their positive and negative electrode materials. In related technologies, carbon materials are often used as the negative electrode material in lithium-ion batteries, and chemical activation is used to attempt to increase porosity. However, chemical activation severely damages the framework structure of carbon materials, affecting not only the pore-forming effect but also reducing the mechanical strength of the carbon materials, thus impacting electrochemical performance.

[0003] Therefore, it is necessary to find a suitable negative electrode material that can maintain high electrochemical performance and good mechanical strength during battery cycling. Summary of the Invention

[0004] In view of this, in order to at least partially solve the aforementioned technical problems, this disclosure provides a porous carbon support and its preparation method, a silicon-carbon composite material and its preparation method, and a battery.

[0005] According to an embodiment of the first aspect of this disclosure, a porous carbon material is provided, comprising: a carbon substrate, the carbon substrate including a pore structure, and nanofibers loaded on the carbon substrate; the pore structure is obtained by creating pores using a two-dimensional template agent, the two-dimensional template agent being a two-dimensional metal hydroxide, and the nanofibers being obtained by crosslinking nanocellulose and metal ions in a metal salt crosslinking agent.

[0006] Optionally, the total pore volume of the porous carbon material is 1~2 cm³. 3 / g.

[0007] Optionally, the specific surface area of ​​the porous carbon material is 2300~2800 m². 2 / g.

[0008] Optionally, the D of porous carbon materials 50 The particle size is 5~20μm.

[0009] According to an embodiment of the second aspect of this disclosure, a method for preparing a porous carbon material is provided, comprising: spray granulation or drying of a slurry containing a carbon source, nanocellulose, a metal salt crosslinking agent, and a two-dimensional template agent to obtain a precursor material; and gradient calcination and washing of the precursor material to obtain a porous carbon material.

[0010] Optionally, the mass ratio of carbon source to two-dimensional template agent is 10:(0.05~3).

[0011] Optionally, the mass ratio of carbon source to nanocellulose is 10:(0.1~3).

[0012] Optionally, the mass ratio of carbon source to metal salt crosslinking agent is 10:(0.01~1).

[0013] Alternatively, the carbon source may include at least one of phenolic resin, pitch, and petroleum coke.

[0014] Optionally, nanocellulose includes at least one of cellulose nanofibers and cellulose nanocrystals.

[0015] Optionally, the nanocellulose includes at least one of cellulose nanocrystal powder with a diameter of 10 nm and a length of 200 nm, or carboxylated nanocellulose with a diameter of 5-10 nm and a length of 1 μm.

[0016] Optionally, the metal ions in the metal salt crosslinking agent include Ca. 2+ Ni 2+ Cu 2+ Ba 2+ 、Sr 2+ and Mg 2+ At least one of them.

[0017] Optionally, the anions in the metal salt crosslinking agent include Cl- - SO4 2- CO3 2- and NO3 - At least one of them.

[0018] Optionally, the two-dimensional template agent is a two-dimensional metal hydroxide.

[0019] Further, optionally, the metal ions in the two-dimensional metal hydroxide include Ni. 2+ Fe 3+ Al 3+ Mg 2+ Co 2+ and Zn 2+ At least one of them.

[0020] Optionally, the two-dimensional metal hydroxide includes at least one of layered monometallic hydroxide, layered bimetallic hydroxide, and layered trimetallic hydroxide.

[0021] Optionally, the thickness of the two-dimensional metal hydroxide is less than or equal to 100 nm.

[0022] Optionally, the thickness of the two-dimensional metal hydroxide is less than 50 nm.

[0023] Further optionally, the thickness of the two-dimensional metal hydroxide is 1 nm, 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm or 45 nm.

[0024] Optionally, when the two-dimensional metal hydroxide includes nickel-iron layered hydroxide nanosheets, the thickness of the two-dimensional metal hydroxide is 3~10 nm, the length is 20~200 nm, and the width is 20~200 nm.

[0025] Optionally, when the two-dimensional metal hydroxide includes sheet-like nano-aluminum hydroxide, the thickness of the two-dimensional metal hydroxide is 3~10 nm.

[0026] Optionally, the mass ratio of carbon source to two-dimensional template agent is 10:0.1, 10:0.2, 10:0.5, 10:1, 10:1.5 or 10:2.

[0027] Optionally, the mass ratio of carbon source to nanocellulose is 10:0.2, 10:0.5, 10:0.8, 10:1, 10:1.5 or 10:2.

[0028] Optionally, the mass ratio of carbon source to metal salt crosslinking agent is 10:0.02, 10:0.05, 10:0.1, 10:0.15, 10:0.2, 10:0.5 or 10:0.8.

[0029] Optionally, the solvent in the slurry is at least one of deionized water, ethanol, and N,N-dimethylformamide.

[0030] Optionally, the solid-liquid ratio in the slurry is (0.1~5):1.

[0031] Further optionally, the solid-liquid ratio in the slurry is 0.25:1, 0.3:1, 0.33:1, 0.5:1 or 1:1.

[0032] Optionally, the slurry may also include a dispersant.

[0033] Optionally, in the slurry, the mass ratio of carbon source to dispersant is 10:(0.1~2).

[0034] Optionally, in the slurry, the mass ratio of carbon source to dispersant is 10:0.2, 10:0.3, 10:0.5 or 10:1.

[0035] Optionally, gradient calcination includes a first stage of calcination and a second stage of calcination; the temperature of the second stage of calcination is higher than the temperature of the first stage of calcination.

[0036] Optionally, the porous carbon material may be sieved after washing.

[0037] Optionally, the temperature of the first stage of calcination is 200~400℃, and the calcination time of the first stage is 1~8h.

[0038] Further optionally, the temperature of the first stage of calcination is 250°C, 300°C, 350°C or 380°C, and the calcination time of the first stage is 2h, 4h, 6h or 7h.

[0039] Optionally, the temperature of the second calcination stage is 450~900℃, and the calcination time is 3~24h.

[0040] Alternatively, the temperature of the second calcination stage is 500℃, 600℃, 650℃, 700℃ or 800℃, and the calcination time is 4h, 6h, 8h or 12h.

[0041] According to an embodiment of the third aspect of this disclosure, a method for preparing a silicon-carbon composite material is provided, comprising subjecting the porous carbon material as described above, or the porous carbon material prepared by the method described above, to silane vapor deposition to obtain the silicon-carbon composite material.

[0042] According to an embodiment of the fourth aspect of this disclosure, a silicon-carbon composite material prepared by the preparation method described above is provided.

[0043] According to an embodiment of the fifth aspect of this disclosure, a battery is provided, including an electrode material comprising at least one of the porous carbon material as described above, a porous carbon material prepared by the preparation method as described above, or a silicon-carbon composite material as described above. Attached Figure Description

[0044] To gain a more complete understanding of this disclosure and its advantages, reference will now be made to the following description taken in conjunction with the accompanying drawings.

[0045] Figure 1 A flowchart illustrating a method for preparing porous carbon materials according to an embodiment of this disclosure is shown;

[0046] Figure 2 A scanning electron microscope image of the porous carbon material prepared in Example 1 of this disclosure is shown;

[0047] Figure 3 A scanning electron microscope image of the porous carbon material prepared in Example 6 of this disclosure is shown;

[0048] Figure 4 A scanning electron microscope image of the porous carbon material prepared in Example 11 of this disclosure is shown;

[0049] Figure 5 A scanning electron microscope image of the porous carbon material prepared in Comparative Example 2 of this disclosure is shown. Detailed Implementation

[0050] The embodiments of the present disclosure will now be described with reference to the accompanying drawings. However, it should be understood that these descriptions are exemplary only and are not intended to limit the scope of the disclosure. In the following detailed description, numerous specific details are set forth to provide a thorough understanding of the embodiments of the present disclosure for ease of explanation. However, it will be apparent that one or more embodiments may be practiced without these specific details. Furthermore, descriptions of well-known structures and techniques are omitted in the following description to avoid unnecessarily obscuring the concepts of the present disclosure.

[0051] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. The term "comprising" as used herein indicates the presence of features, steps, or operations, but does not exclude the presence or addition of one or more other features.

[0052] When using expressions such as "at least one of A, B or C", they should generally be interpreted in accordance with the meaning that is commonly understood by those skilled in the art (e.g., "a system having at least one of A, B or C" should include, but is not limited to, a system having A alone, a system having B alone, a system having C alone, a system having A and B, a system having A and C, a system having B and C, and / or a system having A, B, and C, etc.).

[0053] Lithium-ion batteries play a crucial role in energy storage and are widely used in electric vehicles, portable electronic devices, low-altitude aircraft, and machinery. The charge-discharge performance of lithium-ion batteries is primarily influenced by the cathode and anode materials. Silicon-carbon anode materials, due to their high theoretical specific capacity and low potential plateau, are considered key materials for achieving long-range lithium-ion batteries. Currently, silicon-carbon anode materials prepared using silane porous carbon deposition methods are promising silicon-carbon materials, but the preparation of porous carbon materials still faces many challenges.

[0054] In related technologies, carbon materials for the negative electrode are usually prepared by chemical activation. Although chemical activation can increase the porosity of carbon materials to a certain extent, it is easy to damage the framework structure of carbon materials and reduce their conductivity, thereby affecting their electrochemical performance. In addition, it also affects the mechanical stability of the negative electrode material.

[0055] In realizing the concept of this disclosure, it was discovered that constructing a two-dimensional pore structure within a carbon substrate using a two-dimensional template agent helps to create porous carbon materials with large pore volumes. However, constructing a two-dimensional pore structure can, to some extent, reduce the mechanical strength of the porous carbon material, making it prone to collapse and hindering its continued application in batteries. This disclosure utilizes the cross-linking between nanocellulose and metal salt cross-linking agents to form nanofibers loaded on a carbon substrate, which helps to construct a rigid framework within the carbon substrate, further enhancing the mechanical strength of the porous carbon material.

[0056] In view of this, one aspect of the present disclosure provides a porous carbon material, comprising: a carbon substrate, the carbon substrate including a pore structure, and nanofibers loaded on the carbon substrate; the pore structure is obtained by creating pores using a two-dimensional template agent, the two-dimensional template agent being a two-dimensional metal hydroxide, and the nanofibers being obtained by crosslinking nanocellulose and metal ions in a metal salt crosslinking agent.

[0057] According to embodiments of this disclosure, a two-dimensional template agent is used to precisely construct a two-dimensional pore structure within a carbon substrate. This ensures the uniformity of pore formation, resulting in a high specific surface area, abundant pore structure, and a relatively abundant number of active sites on the outer and inner surfaces of the carbon substrate. For example, when subsequently combined with silicon as an electrode material in a battery, it exhibits high conductivity, increases the deposition of silicon atoms within the pore structure, and thus demonstrates better electrochemical performance during battery cycling. This avoids the high cost and environmental pollution problems associated with alkaline etching for pore formation in related technologies.

[0058] Furthermore, the introduction of the two-dimensional template agent in this disclosure helps guide the attachment of the carbon source, forming a layered three-dimensional structure. Subsequent washing (acid leaching) removes this structure, creating more pore structures (e.g., mesopores and macropores) within the carbon matrix, increasing the total pore volume of the porous carbon material, and allowing the carbon source to fully adhere to both the inner and outer surfaces of the two-dimensional template agent. The nanocellulose of this disclosure crosslinks with metal ions in the metal salt crosslinking agent to form nanofibers, which helps provide a rigid framework for the porous carbon material. This allows the porous carbon material to possess both abundant pore structures and high mechanical strength, improving its cycle stability and electrochemical performance when used as a battery anode.

[0059] In this disclosure, "pore structure" can be understood as a network of tiny, complex, and interconnected pores within a carbon matrix. Such a pore structure can combine pores of different sizes (e.g., macropores, mesopores, micropores, etc.) to increase the specific surface area of ​​the carbon matrix, thereby increasing the number of active sites; at the same time, the aforementioned pore structure enhances the mass transfer effect when used as an electrode in a battery.

[0060] In this disclosure, "two-dimensional template agent" can be understood as a material with a layered or plate-like microstructure. During the formation of porous carbon material, carbon source can fill or cover the surface and gaps of the two-dimensional template agent. Subsequently, the two-dimensional template agent is removed through carbonization or washing. The two-dimensional shape of the two-dimensional template agent is retained in the porous carbon material, thereby forming a two-dimensional pore structure.

[0061] In this disclosure, "nanofiber loaded on a carbon substrate" can be understood as nanofibers loaded on the surface of a carbon substrate or in the porous structure of a carbon substrate.

[0062] Considering that if the total pore volume of the porous carbon material is too small, the number of active sites provided will be limited, resulting in limited improvement in battery performance of the electrode material; if the total pore volume is too large, the pore structure may collapse during cycling, affecting cycle performance. Therefore, in some embodiments of this disclosure, the total pore volume of the porous carbon material is 1~2 cm³. 3 / g. It can be understood that a total pore volume within the aforementioned range results in a richer internal pore structure in the porous carbon material. Combined with the channel structure formed by the two-dimensional template agent, this leads to a porous carbon material with a large pore capacity. When subsequently used as an electrode in a battery, it can adsorb a relatively large number of ions. Especially when applied in lithium-ion batteries, the large pore volume provides more active sites for lithium-ion insertion and extraction, as well as surface adsorption, which helps to improve the discharge specific capacity and cycle performance of the electrode material.

[0063] Optionally, the total pore volume of the porous carbon material can be, for example, 1 cm³. 3 / g, 1.1cm 3 / g, 1.13cm 3 / g, 1.4cm 3 / g, 1.15cm 3 / g, 1.16cm 3 / g, 1.17cm 3 / g, 1.2cm 3 / g, 1.3cm 3 / g, 1.4cm 3 / g, 1.5cm 3 / g, 1.6cm 3 / g, 1.7cm 3 / g, 1.8cm 3 / g, 1.9cm 3 / g or 2cm 3 / g, or a range consisting of any two of the above values, preferably 1.1~1.3cm 3 / g.

[0064] Considering that if the total specific surface area of ​​porous carbon is too small, the surface adsorption space provided will be limited, thus limiting the improvement of battery performance of the electrode material, in some embodiments of this disclosure, the specific surface area of ​​the porous carbon material is 2300~2800 m². 2 / g. This configuration, based on a larger specific surface area, increases the interfacial area between the electrode material and the electrolyte during subsequent use as electrode material in the battery. This provides more active sites for charge storage and sufficient interfaces for lithium ion adsorption, significantly improving the electrochemical reaction rate and extending the battery's cycle life.

[0065] Optionally, the specific surface area of ​​the porous carbon material can be, for example, 2300 m². 2 / g、2400m 2 / g、2450m 2 / g、2500m 2 / g、2550m 2 / g、2600m 2 / g、2650m 2 / g、2700m 2 / g or 2800m 2 / g, or a range consisting of any two of the above values. Preferably, it is 2400~2700m. 2 / g.

[0066] In some embodiments, the D of porous carbon materials 50 The particle size is 5~20μm. D 50 The particle size can be understood as the median particle size of the porous carbon material. This setting provides the porous carbon material with good flowability and dispersibility, which helps it to have relatively stable ion transport performance when used as an electrode material in batteries. 50 Particle size can generally be obtained by measuring with a laser particle size analyzer.

[0067] Optionally, the D of porous carbon materials 50 The particle size can be, for example, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm or 20 μm, or a range consisting of any two of the above values.

[0068] Another aspect of this disclosure provides a method for preparing porous carbon materials. Figure 1 A flowchart illustrating a method for preparing porous carbon materials according to embodiments of this disclosure is shown, such as... Figure 1 As shown, the preparation method includes operations S101 to S102.

[0069] In operation S101, a slurry containing a carbon source, nanocellulose, metal salt crosslinking agent, and two-dimensional template agent is spray-granulated or dried to obtain a precursor material.

[0070] In operation S102, the precursor material is subjected to gradient calcination and washing to obtain porous carbon material.

[0071] According to embodiments of this disclosure, porous carbon materials are prepared using a carbon source, nanocellulose, a metal salt crosslinking agent, and a two-dimensional template agent as raw materials. The introduction of the two-dimensional template agent allows for the precise construction of a two-dimensional macroporous structure within the carbon material. Nanocellulose can crosslink with metal ions in the metal salt crosslinking agent to form high-strength fine fibers, creating a rigid framework within the carbon source. This effectively enhances the mechanical strength of the carbon particles and, during calcination, forms even stronger nanofibers, significantly improving the compressive strength and breakage resistance of the porous carbon material. Through synergistic effects, the prepared porous carbon material possesses not only large pore volume and high specific surface area but also high mechanical strength. When subsequently combined with silicon, it exhibits superior electrochemical performance, effectively avoiding the problems of high cost, heavy pollution, uncontrollable pore structure, and poor mechanical strength associated with traditional strong alkali etching methods for preparing porous carbon materials.

[0072] The preparation method disclosed herein is simple, low-cost, environmentally friendly, and efficient, and has a strong ability to control the pore structure.

[0073] It is understandable that carbon source generally refers to raw materials that can be converted into carbon materials through calcination.

[0074] In some embodiments, the carbon source includes at least one of phenolic resin, pitch, and petroleum coke, preferably phenolic resin or petroleum coke. The phenolic resin may be a thermosetting phenolic resin.

[0075] It is understandable that nanocellulose generally refers to cellulose-based materials with a diameter of less than 100nm.

[0076] In some embodiments, nanocellulose includes at least one of cellulose nanofibers (CNF) and cellulose nanocrystals (CNC).

[0077] In one specific embodiment, the nanocellulose is a cellulose nanocrystal powder with a diameter of 10 nm and a length of 200 nm.

[0078] In one specific embodiment, the nanocellulose is carboxylated nanocellulose with a diameter of 5-10 nm and a length of 1 μm.

[0079] In some embodiments, the metal ions in the metal salt crosslinking agent include Ca. 2+ Ni 2+ Cu 2+ Ba 2+ 、Sr 2+ and Mg 2+At least one of the following. The anion in the metal salt crosslinking agent can be a conventional acid radical ion in the art, preferably including Cl. - SO4 2- CO3 2- and NO3 - At least one of them.

[0080] In some specific implementations, the metal salt crosslinking agent is nickel chloride or calcium chloride.

[0081] In some embodiments, the two-dimensional template agent is preferably a two-dimensional metal hydroxide.

[0082] It is understood that the two-dimensional metal hydroxides in this disclosure may be one or a combination of layered monometallic hydroxides, layered bimetallic hydroxides, and layered trimetallic hydroxides.

[0083] In some further embodiments, the metal ions in the two-dimensional metal hydroxide may include Ni. 2+ Fe 3 + Al 3+ Mg 2+ Co 2+ and Zn 2+ At least one of them.

[0084] Optionally, the thickness of the two-dimensional metal hydroxide is less than or equal to 100 nm, preferably less than 50 nm, for example, it can be 1 nm, 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm or 45 nm.

[0085] Furthermore, the two-dimensional metal hydroxide can be, for example, at least one of nickel-iron layered hydroxide nanosheets (NiFe-LDH nanosheets) or sheet-like nano-aluminum hydroxide.

[0086] In some further embodiments, when the two-dimensional metal hydroxide includes nickel-iron layered hydroxide nanosheets, the two-dimensional metal hydroxide has a thickness of 3-10 nm, a length of 20-200 nm, and a width of 20-200 nm.

[0087] In the case of two-dimensional metal hydroxides including sheet-like nano-aluminum hydroxide, the thickness of the two-dimensional metal hydroxide is 3~10 nm.

[0088] It is understood that the two-dimensional metal hydroxides disclosed herein can be purchased directly from commercial sources or prepared using conventional methods in the art.

[0089] In some embodiments, the method for preparing two-dimensional metal hydroxides preferably includes the following steps: subjecting a solution containing the corresponding metal salt to a solvothermal reaction.

[0090] Furthermore, the solvent in the solution containing the corresponding metal salt is preferably an alcohol solvent, such as at least one of methanol, isopropanol, and glycerol. The concentration of the metal salt in the solution can be conventional in the art; the metal salt can be at least one of nitrate, hydrochloride, and sulfate.

[0091] Solvothermal reactions typically require the reactants to be placed in a polytetrafluoroethylene (PTFE)-lined reactor, which is then heated in an oven or sintering furnace (e.g., a muffle furnace). The percentage of the reactor liner's volume containing the corresponding metal salt is conventional in this field.

[0092] The temperature of the solvothermal reaction can be 160~300℃, for example 180℃, 200℃, 220℃, 240℃ or 250℃; the time of the solvothermal reaction can be 1~12h, for example 1h, 2h, 4h, 6h or 8h.

[0093] In one specific embodiment, when the two-dimensional metal hydroxide is NiFe-LDH nanosheets, the metal salt is a nickel salt (e.g., nickel nitrate) and an iron salt (e.g., ferric nitrate) in a molar ratio of 1:1, the solvent is isopropanol and glycerol in a volume ratio of 1:1, the sum of the concentrations of the nickel salt and the iron salt is 0.2M, the temperature of the solvothermal reaction is 180°C, and the reaction time is 6h.

[0094] In one specific embodiment, when the two-dimensional metal hydroxide is sheet-like nano-aluminum hydroxide, the metal salt is anhydrous aluminum chloride, the solvent is anhydrous methanol, the mass ratio of the metal salt to the solvent is 1:64, the temperature of the solvothermal reaction is 240°C, and the reaction time is 1 hour.

[0095] After the aforementioned solvothermal reaction is completed, washing and drying are generally required. The washing solvent can be conventional in the art, such as deionized water.

[0096] The calcination disclosed herein is carried out under the protection of an inert gas, which refers to a gas that generally does not react with the reactants, such as nitrogen or argon.

[0097] The introduction of a two-dimensional template helps guide the adhesion of the carbon source, forming a layered three-dimensional structure. This allows for the creation of more porous structures (e.g., mesopores and macropores) in the carbon substrate during gradient calcination and washing, increasing the total pore volume of the porous carbon material and enabling the carbon source to fully adhere to both the inner and outer surfaces of the two-dimensional template. Therefore, in some embodiments, the mass ratio of carbon source to two-dimensional template is 10:(0.05~3).

[0098] Optionally, the mass ratio of carbon source to two-dimensional template agent can be, for example, 10:0.1, 10:0.2, 10:0.5, 10:1, 10:1.5 or 10:2, or a range consisting of any two of the above ratios.

[0099] Preferably, the mass ratio of carbon source to two-dimensional template agent is 10:(0.1~1), for example, 10:0.1 or 10:0.5. This setting helps to construct a larger pore capacity and specific surface area in the carbon substrate using the two-dimensional template agent.

[0100] In some embodiments, the mass ratio of carbon source to nanocellulose can be 10:(0.1~3), for example, 10:0.2, 10:0.5, 10:0.8, 10:1, 10:1.5 or 10:2, or a range consisting of any two of the above ratios. Preferably, it is 10:(0.5~2), for example, 10:0.5 or 10:1.

[0101] In some embodiments, the mass ratio of carbon source to metal salt crosslinking agent can be 10:(0.01~1), for example, 10:0.02, 10:0.05, 10:0.1, 10:0.15, 10:0.2, 10:0.5 or 10:0.8, or a range consisting of any two of the above ratios. Preferably, it is 10:(0.02~0.5), for example, 10:0.05.

[0102] In some embodiments, the solvent in the slurry may be at least one of deionized water, ethanol, and N,N-dimethylformamide (DMF).

[0103] In one specific embodiment, the solvent in the slurry is a mixture of deionized water and anhydrous ethanol in a mass ratio of 3:1.

[0104] In some embodiments, the solid-liquid ratio in the slurry may be (0.1~5):1, preferably (0.2~2):1, for example 0.25:1, 0.3:1, 0.33:1, 0.5:1 or 1:1. The solid-liquid ratio refers to the mass ratio of substances other than solvent in the slurry to the mass of solvent.

[0105] In some embodiments, to enhance the dispersibility of the system, the slurry preferably also includes a dispersant. A dispersant can be understood as a surfactant with both lipophilic and hydrophilic properties, capable of uniformly dispersing difficult-to-dissolve solid particles in a liquid at the molecular level, while preventing sedimentation and aggregation, thus ensuring the formation of a stable suspension.

[0106] In some embodiments, the dispersant may be at least one of polyethylene glycol (PEG), polyvinylpyrrolidone (PVP), and polyvinyl alcohol (PVA), preferably PVP. The mass ratio of carbon source to dispersant may be 10:(0.1~2), for example 10:0.2, 10:0.3, 10:0.5, or 10:1.

[0107] It is understood that the preparation method of the slurry can be conventional in the field, generally involving mixing all raw materials evenly. Preferably, it includes the following steps: first, mixing all raw materials except the solvent for the first time, and then adding the solvent for the second mixing.

[0108] The type and amount of solvent are as described above. It is preferable to add the solvent in batches, more preferably in 3 to 5 portions.

[0109] It should be noted that the first and / or second mixing can be carried out in a manner conventional in the art, such as mixing in a mixer or agitator. Preferably, the first mixing is carried out in a mixer. The first mixing time can be 5 to 60 minutes, for example, 10 minutes, 20 minutes, or 30 minutes. The second mixing time can be 3 to 30 minutes, for example, 5 minutes or 10 minutes.

[0110] In one specific implementation, the first mixing is carried out in a mixer, and the second mixing is carried out in a stirrer.

[0111] In some further embodiments, the first mixing is carried out in a mixer for 5 to 60 minutes, and the second mixing is carried out in an agitator at a speed of 500 to 1000 rpm for 3 to 30 minutes.

[0112] In some embodiments, spray granulation is generally carried out in a spray dryer. During spray granulation, the inlet temperature of the spray dryer can be 150~220°C, for example 180°C, 200°C, or 210°C; the outlet temperature can be 80~140°C, for example 100°C, 110°C, or 120°C; the nozzle diameter can be 0.4~1mm, for example 0.5mm, 0.7mm, or 0.8mm; the spray pressure can be 0.1~0.4MPa, 0.2MPa, 0.3MPa, or 0.4MPa; and the feed rate can be 8~12mL / min, for example 9mL / min, 10mL / min, or 11mL / min. After spray granulation, drying is generally required. The drying operation and conditions can be conventional in the art; the drying temperature can be 70~120°C, for example 80°C or 100°C; and the drying time can be 6~24h, for example 8h, 10h, or 12h.

[0113] In one specific implementation, during the spray granulation process, the spray dryer has an inlet temperature of 200°C, an outlet temperature of 110°C, a nozzle diameter of 0.7 mm, a spray pressure of 0.3 MPa, and a feed rate of 10 mL / min.

[0114] In some embodiments, the drying method may be oven drying. Drying may be carried out, for example, in a vacuum dryer. Drying is preferably carried out under vacuum conditions. The drying temperature may be 80~150°C, for example 100°C, 120°C or 130°C; the drying time may be 6~24h, for example 8h, 12h or 16h.

[0115] In some implementations, gradient calcination is typically carried out under an inert atmosphere. An inert atmosphere generally refers to a gas that does not react with the reactants, such as nitrogen or argon.

[0116] In this disclosure, "gradient calcination" refers to calcination where, after the previous calcination stage is completed, no cooling treatment is required, and the temperature is directly increased to the temperature of the next calcination stage based on the previous calcination temperature.

[0117] In some embodiments, gradient calcination includes a first stage of calcination and a second stage of calcination; as previously mentioned, the temperature of the second stage of calcination is higher than the temperature of the first stage of calcination. Gradient calcination can avoid structural collapse caused by excessively rapid heating, and the mechanical strength of carbon materials is improved by first cross-linking at a low temperature and then carbonizing at a high temperature.

[0118] In some embodiments, the rate of heating to the first calcination temperature can be 1~10℃ / min, for example 2℃ / min or 5℃ / min; the first calcination temperature can be 200~400℃, for example 250℃, 300℃, 350℃ or 380℃; the first calcination time can be 1~8h, for example 2h, 4h, 6h or 7h. The rate of heating to the second calcination temperature can be 1~10℃ / min, for example 2℃ / min or 5℃ / min; the second calcination temperature can be 450~900℃, for example 500℃, 600℃, 650℃, 700℃ or 800℃; the second calcination time can be 3~24h, for example 4h, 6h, 8h or 12h.

[0119] In some embodiments, gradient calcination may include the following process: first calcining at 200~400℃ for 1~8h, and then continuing to calcining at 450~900℃ for 3~24h.

[0120] In one specific implementation, gradient calcination includes the following process: first calcining at 300°C for 2 hours, and then continuing to calcinate at 700°C for 6 hours.

[0121] Therefore, the mechanical strength and electrochemical activity of porous carbon materials can be controlled through the gradient calcination process described above.

[0122] In operation S102, washing is generally acid washing to remove the two-dimensional template agent. The acid used for acid washing may include at least one of sulfuric acid, hydrochloric acid, oxalic acid, phosphoric acid, hydrofluoric acid, and acetic acid. The concentration of the acid used for acid washing can be 0.1~5M, for example 1M or 2M. The acid washing time can be 20~90 min, for example 30 min, 40 min, or 60 min. The amount of acid used in the acid washing process can be conventional in the art, generally enough to immerse the porous carbon material. Acid washing is generally carried out under mixed conditions (e.g., ultrasonic or agitated). After acid washing, rinsing with deionized water is generally required.

[0123] In some embodiments, the porous material is typically dried and sieved after washing. The drying temperature can be 70~120°C, for example 80°C, 100°C or 110°C; the drying time can be 6~24h, for example 8h or 12h.

[0124] Another aspect of this disclosure provides a method for preparing a silicon-carbon composite material, comprising subjecting a porous material as described above or a porous material prepared by the method described above to silane vapor deposition to obtain a silicon-carbon composite material.

[0125] According to embodiments of this disclosure, in silicon-carbon composite materials, the porous structure and nanofibers constructed based on porous carbon materials facilitate silicon deposition on the surface due to the large pore volume and specific surface area of ​​the pore structure. This provides more active sites and electrolyte contact interface area for charge storage and transport, significantly improving the electrochemical reaction rate and extending the battery's cycle life. This disclosure utilizes nanofibers formed by crosslinking between nanocellulose and salt crosslinking agents to construct a rigid framework. A uniformly controlled macroporous pore structure is formed using a two-dimensional template agent, effectively avoiding the use of strong alkali etching for pore creation. This not only solves the problems of high cost, heavy pollution, and uncontrollable pore structure in the preparation of porous carbon materials using traditional alkali etching, but also significantly improves the mechanical strength and electrochemical performance of porous carbon materials, laying a solid foundation for the commercial application of silicon-carbon anode materials. In this disclosure, the temperature for silane vapor deposition can be 400~600℃, for example, 500℃. The time for silane vapor deposition can be 1~4h, for example, 2h.

[0126] In some embodiments, silane vapor deposition is preferably carried out in a mixture of silane and an inert gas. The silane flow rate is preferably 10–50 sccm, for example, 20 sccm, 25 sccm, or 30 sccm. The inert gas flow rate is preferably 30–80 sccm, for example, 40 sccm, 50 sccm, or 60 sccm. The total pressure of the mixed gas can be 100–2000 Pa, for example, 200 Pa, 300 Pa, or 500 Pa.

[0127] In some embodiments, the porous carbon material is typically activated prior to silane vapor deposition. Activation preferably includes the following process: placing the porous carbon material in a sintering furnace for vacuum degassing, followed by calcination.

[0128] In some implementations, vacuum degassing typically requires evacuating to a vacuum level of 5 × 10⁻⁶. -3 Below Pa. Calcination is generally carried out under an inert atmosphere. The calcination temperature can be 300~500℃, for example 400℃. The calcination time can be 0.5~4h, for example 1h or 2h. According to convention in the art, after calcination, silane vapor deposition is generally performed directly by raising or lowering the temperature to the silane vapor deposition temperature based on the calcination temperature.

[0129] Another aspect of this disclosure is to provide a silicon-carbon composite material prepared by the aforementioned preparation method.

[0130] According to the embodiments of this disclosure, the beneficial effects of the silicon-carbon composite material of this disclosure are consistent with the beneficial effects of the aforementioned porous carbon material, and will not be repeated here.

[0131] Another aspect of this disclosure provides a battery including an electrode material comprising at least one of the porous carbon material as described above, a porous carbon material prepared by the preparation method described above, or a silicon-carbon composite material as described above.

[0132] According to the embodiments of this disclosure, the beneficial effects of the battery of this disclosure are consistent with the beneficial effects of the aforementioned porous carbon materials and / or silicon-carbon composite materials, and will not be repeated here.

[0133] It is understandable that the aforementioned porous carbon materials or silicon-carbon composite materials can be used as the negative electrode of a battery.

[0134] In one specific embodiment, a slurry is formed by mixing silicon-carbon composite material with binder (such as polyimide or sodium carboxymethyl cellulose), conductive agent (such as conductive carbon black or carbon nanotubes), solvent (such as NMP or water), etc., and then coating it onto a copper foil current collector to obtain a negative electrode sheet.

[0135] Furthermore, the mass ratio of silicon-carbon composite material, conductive agent, and binder can be 8:1:1.

[0136] This disclosure does not impose any particular limitations on the positive electrode of the battery, such as lithium nickel cobalt manganese oxide, lithium iron phosphate, etc.

[0137] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain the various preferred embodiments of this disclosure.

[0138] All reagents and raw materials used in this disclosure are commercially available.

[0139] The positive and progressive effects of this disclosure are as follows:

[0140] The porous carbon material prepared in this disclosure not only has a uniform pore distribution but also possesses large pore volume, high specific surface area, and excellent mechanical strength and electrochemical performance, laying a solid foundation for the commercial application of silicon-carbon anode materials. Furthermore, the preparation method is simple, low-cost, environmentally friendly, efficient, and has strong controllability of pore structure, effectively avoiding the problems of high cost, heavy pollution, and uncontrollable pore structure that exist in the preparation of porous carbon materials using traditional strong alkali etching.

[0141] The following examples and comparative examples illustrate the implementation of this disclosure in more detail. It should be noted that the specific embodiments described below are merely illustrative and are not intended to limit the scope of this disclosure.

[0142] Example 1:

[0143] Step (1) Preparation process of nickel-iron layered hydroxide nanosheets (hereinafter referred to as NiFe-LDH nanosheets):

[0144] Nickel nitrate hexahydrate (Ni(NO3)2·6H2O, purity ≥98%, Sigma-Aldrich) and iron nitrate nonahydrate (Fe(NO3)3·9H2O, purity ≥97%, Aladdin) were dissolved in isopropanol in a molar ratio of 1:1 to prepare a mixed metal salt solution with a total concentration of 0.2M.

[0145] After adding an equal volume of glycerol to the mixed metal salt solution, the solution was transferred to a polytetrafluoroethylene-lined reactor and reacted at 180°C for 6 hours. After natural cooling, the solution was filtered and washed three times with deionized water, and then vacuum dried at 60°C for 6 hours to obtain the dried product. The dried product was dissolved in sufficient ammonia water, transferred to a reactor, placed in an oven, and reacted at 90°C for 4 hours. After natural cooling to room temperature, the product was washed twice each with distilled water and ethanol, and then dried to obtain NiFe-LDH nanosheets. The thickness of these nanosheets was measured to be 3–10 nm, the length 20–200 nm, and the width 20–200 nm.

[0146] Step (2) Preparation of the mixed slurry:

[0147] 100 parts by weight of thermosetting phenolic resin (model PF-660, solid content ≥98%), 5 parts by weight of cellulose nanocrystal powder (CNC, diameter 10nm, length 200nm, Sigma-Aldrich), 1.5 parts by weight of NiCl2 (analytical grade, Sinopharm), 15 parts by weight of NiFe-LDH nanosheets, and 3 parts by weight of polyvinylpyrrolidone (PVP-K30, Sigma-Aldrich) were added to a mechanical mixer and mixed for 10 minutes to initially disperse the raw materials evenly, thus obtaining a mixture.

[0148] Add the solvent (a mixture of 300 parts by weight of homemade deionized water and 100 parts by weight of anhydrous ethanol) to the mixture in three portions. After each addition, stir with a magnetic stirrer at 800 rpm for 5 minutes to ensure that the mixture and solvent are fully mixed to form a uniform black slurry with a solid-liquid ratio of approximately 1:3.

[0149] Step (3) Preparation process of precursor particles:

[0150] The prepared mixed slurry was transported to a spray dryer (model LPG-5, inlet temperature controllable range 50~300℃) using a peristaltic pump. The spray dryer parameters were set as follows: inlet temperature 200℃, outlet temperature 110℃, nozzle diameter 0.7mm, spray pressure 0.3MPa, and feed rate 10mL / min. Spray granulation was performed under these parameters, and the dried precursor particles were collected, with a particle size distribution between 50~200μm. The collected precursor particles were transferred to an oven and dried at 80℃ for 10 hours until the moisture content of the precursor particles was less than 1%.

[0151] Step (4) Preparation process of porous carbon materials:

[0152] The dried precursor particles were evenly spread in an alumina crucible, which was then placed in a sintering furnace (Bangshida, model BSDS-1200). Pre-carbonization was first performed under a nitrogen atmosphere, with the temperature increased to 300℃ at a rate of 5℃ / min and held for 2 hours to form a pre-carbonized product. Then, under a nitrogen atmosphere, the temperature was further increased from 300℃ to 700℃ at a rate of 5℃ / min and held for 6 hours for carbonization. After the reaction was complete, the sample was cooled to room temperature and removed.

[0153] Step (5) Washing:

[0154] The calcined carbonized sample was immersed in 1M hydrochloric acid and stirred for 1 hour. After filtration, it was added to deionized water and washed three times with a magnetic stirrer at 500 rpm until the pH of the filtrate was above 5. The sample was then centrifuged at 5000 rpm for 10 minutes, and the solid fraction was collected. The collected solid was dried in an oven at 80℃ for 8 hours to remove residual moisture. The sample was then vibrated and classified using a sieve to obtain the particle size D. 50 It is a porous carbon material with a diameter of 10~20μm.

[0155] Example 2:

[0156] The preparation process of Example 2 is largely the same as that of Example 1, except that the thermosetting phenolic resin in the mixed slurry is replaced with petroleum coke (Henglin Minerals, 40 mesh).

[0157] Example 3:

[0158] The preparation process of Example 3 is largely the same as that of Example 1, except that NiFe-LDH nanosheets are replaced with sheet-like nano-aluminum hydroxide.

[0159] The preparation process of sheet-like nano-aluminum hydroxide is as follows:

[0160] Anhydrous aluminum chloride and anhydrous methanol were directly placed into a polytetrafluoroethylene (PTFE) reactor at a mass ratio of 1:64. After a vigorous reaction at room temperature to form a transparent and colorless solution, the PTFE reactor was sealed and placed in a muffle furnace and kept at 240°C for 1 hour. After the reaction was complete, the PTFE reactor was removed and allowed to cool naturally to room temperature to obtain nanosheet aluminum hydroxide with a thickness of 3-10 nm.

[0161] Example 4:

[0162] The preparation process of Example 4 is largely the same as that of Example 1, except that NiCl2 in the mixed slurry is replaced with CaCl2.

[0163] Example 5:

[0164] The preparation process of Example 5 is largely the same as that of Example 1, except that the cellulose nanocrystal powder in the mixed slurry is replaced with carboxylated nanocellulose (CNF, diameter 5~10nm, length 1μm, Seruna).

[0165] Example 6:

[0166] The preparation process of Example 6 is largely the same as that of Example 1, except that the amount of cellulose nanocrystal powder in the mixed slurry is adjusted to 20 parts by mass.

[0167] Example 7:

[0168] The preparation process of Example 7 is largely the same as that of Example 1, except that the amount of NiCl2 in the mixed slurry is adjusted to 0.5 parts by mass.

[0169] Example 8:

[0170] The preparation process of Example 8 is largely the same as that of Example 1, except that the amount of NiFe-LDH nanosheets in the mixed slurry is adjusted to 5 parts by mass.

[0171] Example 9:

[0172] The preparation process of Example 9 is largely the same as that of Example 1, except that the carbonization temperature in the preparation process of porous carbon material is adjusted from 700℃ to 500℃.

[0173] Example 10:

[0174] The preparation process of Example 10 is largely the same as that of Example 1, except that the carbonization holding time in the preparation process of porous carbon material is adjusted from 6 hours to 4 hours.

[0175] Example 11:

[0176] The preparation process of Example 11 is largely the same as that of Example 1, except that the spray granulation step in the preparation of precursor particles is changed to vacuum drying at 120°C.

[0177] Comparative Example 1:

[0178] The preparation process of Comparative Example 1 is largely the same as that of Example 1, except that NiFe-LDH nanosheets were not added during the preparation of the mixed slurry.

[0179] Comparative Example 2:

[0180] The preparation process of Comparative Example 2 is largely the same as that of Example 1, except that cellulose nanocrystal powder was not added during the preparation of the mixed slurry.

[0181] Comparative Example 3:

[0182] The preparation process of Comparative Example 3 is largely the same as that of Example 1, except that NiCl2 was not added during the preparation of the mixed slurry.

[0183] Comparative Example 4:

[0184] The preparation process of Comparative Example 4 is largely the same as that of Example 1, except that NiFe-LDH nanosheets and cellulose nanocrystal powder were not added during the preparation of the mixed slurry.

[0185] Comparative Example 5:

[0186] The preparation process of Comparative Example 5 is largely the same as that of Example 1, except that the carbonization preparation process of porous carbon material is replaced by the following single carbonization process, and the subsequent washing process is the same as that of Example 1.

[0187] One carbonization process: The dried precursor particles are evenly spread in an alumina crucible, and the crucible is placed in a sintering furnace. Under a nitrogen atmosphere, the temperature is raised to 700℃ at a heating rate of 5℃ / min and held for 6 hours. After the reaction is complete, the mixture is cooled to room temperature and the carbonized sample is removed.

[0188] The porous carbon materials prepared in Examples 1 to 11 and Comparative Examples 1 to 5 were characterized by scanning electron microscopy.

[0189] Figure 2 A scanning electron microscope image of the porous carbon material prepared in Example 1 of this disclosure is shown; Figure 3 A scanning electron microscope image of the porous carbon material prepared in Example 6 of this disclosure is shown; Figure 4 A scanning electron microscope image of the porous carbon material prepared in Example 11 of this disclosure is shown; Figure 5 A scanning electron microscope (SEM) image of the porous carbon material prepared in Comparative Example 2 of this disclosure is shown. (See image.) Figure 5 It can be seen that in Comparative Example 2, due to the lack of added nanocellulose porous carbon, there is more particle breakage. Figure 3 Due to the addition of more nanocellulose, the porous carbon spheres have a higher surface roughness. Figure 5 For amorphous porous carbon that has not been spray-granulated, such as Figure 2 It can be seen that the porous carbon spheres formed are relatively regular and have a relatively complete shape.

[0190] The porous carbon materials prepared in Examples 1 to 11 and Comparative Examples 1 to 5 were tested using an ASAP2020 surface area and pore size analyzer. The test results are shown in Table 1.

[0191] Silicon-carbon composite materials were prepared by silane deposition using the porous carbon materials obtained in Examples 1-11 and Comparative Examples 1-5, respectively. The preparation process is as follows: The porous carbon materials obtained above were placed in a tube furnace for vacuum degassing, and the vacuum was evacuated to 5×10⁻⁶. -3 At 50 sccm, argon gas was introduced and the temperature was raised to 400℃ and held for 1 hour. Silane deposition was then carried out in a mixture of silane and argon gas at 500℃, with a silane gas flow rate of 20 sccm, an argon gas flow rate of 100 sccm, a total pressure of 200 Pa, and a deposition time of 120 minutes. After deposition, the mixture was sealed and stored in a glove box to obtain a silicon-carbon composite material.

[0192] The silicon-carbon composite materials prepared from the porous carbon materials of Examples 1 to 11 and Comparative Examples 1 to 5 were subjected to electrochemical tests, and the test process is shown below.

[0193] Silicon-carbon composite material, conductive carbon black, and sodium carboxymethyl cellulose were mixed in a mass ratio of 80:10:10, and deionized water was added to form a slurry. The slurry was then coated onto 10 μm thick copper foil and vacuum dried at 120°C for 12 hours. The resulting electrode was then die-cut into 12 mm diameter sheets. The negative electrode was metallic lithium. A CR2032 button cell was assembled in an argon glove box using a 1 mol / L LiPF6 electrolyte (solvents consisting of ethylene carbonate (EC), dimethyl carbonate (DMC), and fluoroethylene carbonate (FEC), with EC:DMC = 1:1 (volume ratio) and FEC comprising 5% of the total solvent volume). Constant current charge / discharge tests were performed on a LAND CT2001A battery testing system, with a test voltage range of 0.01~1.5V (vs. Li / Li). + The current density was 0.1C (1C=2000mA / g), and the test results are shown in Table 1 below.

[0194] Table 1

[0195]

[0196] As shown in Table 1, the silicon-carbon composite material formed from the porous carbon material prepared in this disclosure not only has a larger pore volume and a larger specific surface area compared to the comparative examples, but also exhibits better 0.2C discharge specific capacity and 2C cycle retention. In Comparative Example 1, due to the absence of nano-two-dimensional metal hydroxide, it is difficult to form a porous structure, resulting in lower pore volume and specific surface area, and a smaller amount of silicon atoms deposited within the pores, leading to poorer capacity and cycle life of the silicon-carbon composite material. In Comparative Example 2, the absence of nano-cellulose reduces the stability of the porous carbon structure, resulting in decreased pore volume, specific surface area, and cycle performance. In Comparative Example 3, the absence of a metal salt crosslinking agent makes it difficult for cellulose nanocrystals to crosslink and form a high-strength fiber structure, reducing the stability of the porous carbon structure and consequently significantly reducing the capacity and cycle life of the silicon-carbon composite material. In Comparative Example 4, the absence of both nano-two-dimensional metal hydroxide and nano-cellulose results in a significant reduction in both specific surface area and pore volume. Comparative Example 5, due to the lack of gradient calcination, resulted in rapid thermal decomposition of nanocellulose, making it difficult to form a high-strength carbon fiber structure. This reduced the stability of the porous carbon structure and decreased the specific capacity and cycle life of the silicon-carbon anode material.

[0197] The specific embodiments described above further illustrate the purpose, technical solutions, and beneficial effects of this disclosure. It should be understood that the above descriptions are merely specific embodiments of this disclosure and are not intended to limit this disclosure. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this disclosure should be included within the protection scope of this disclosure.

Claims

1. A porous carbon material, comprising: carbon substrate, The carbon substrate includes a porous structure, and nanofibers are loaded on the carbon substrate. The pore structure is obtained by gradient calcination and washing of the precursor material to remove the two-dimensional template agent, which is a two-dimensional metal hydroxide. The precursor material is obtained by spray granulation or drying of a slurry containing a carbon source, nanocellulose, metal salt crosslinking agent, and two-dimensional template agent. The nanofibers are obtained by crosslinking the nanocellulose in the precursor material with metal ions in the metal salt crosslinking agent.

2. The porous carbon material according to claim 1, wherein, The porous carbon material satisfies one or more of the following conditions: The total pore volume of the porous carbon material is 1~2 cm³. 3 / g; The specific surface area of ​​the porous carbon material is 2300~2800 m². 2 / g; The porous carbon material D 50 The particle size is 5~20μm.

3. A method for preparing a porous carbon material as described in claim 1 or 2, comprising: A slurry containing a carbon source, nanocellulose, metal salt crosslinking agent, and two-dimensional template agent is spray-granulated or dried to obtain a precursor material. The precursor material is subjected to gradient calcination and washing to obtain the porous carbon material.

4. The preparation method according to claim 3, wherein, Each component in the slurry satisfies one or more of the following conditions: The mass ratio of the carbon source to the two-dimensional template agent is 10:(0.05~3). The mass ratio of the carbon source to the nanocellulose is 10:(0.1~3). The mass ratio of the carbon source to the metal salt crosslinking agent is 10:(0.01~1).

5. The preparation method according to claim 3, wherein, Each component in the slurry satisfies one or more of the following conditions: The carbon source includes at least one of phenolic resin, asphalt, and petroleum coke; The nanocellulose includes at least one of cellulose nanofibers and cellulose nanocrystals; The nanocellulose includes at least one of cellulose nanocrystal powder with a diameter of 10 nm and a length of 200 nm, or carboxylated nanocellulose with a diameter of 5-10 nm and a length of 1 μm. The metal ions in the metal salt crosslinking agent include Ca. 2+ Ni 2+ Cu 2+ Ba 2+ 、Sr 2+ and Mg 2+ At least one of them; The anions in the metal salt crosslinking agent include Cl. - SO4 2- CO3 2- and NO3 - At least one of them; The two-dimensional template agent is a two-dimensional metal hydroxide.

6. The preparation method according to claim 5, wherein, The two-dimensional metal hydroxide satisfies one or more of the following conditions: The metal ions in the two-dimensional metal hydroxide include Ni. 2+ Fe 3+ Al 3+ Mg 2+ Co 2+ and Zn 2+ At least one of them; The two-dimensional metal hydroxide includes at least one of layered monometallic hydroxide, layered bimetallic hydroxide, and layered trimetallic hydroxide; The two-dimensional metal hydroxide includes at least one of nickel-iron layered hydroxide nanosheets and sheet-like nano-aluminum hydroxide. The size of the two-dimensional metal hydroxide is selected from one of the following combinations: The thickness of the two-dimensional metal hydroxide is less than or equal to 100 nm; The thickness of the two-dimensional metal hydroxide is less than 50 nm; The thickness of the two-dimensional metal hydroxide is 1 nm, 3 nm, 5 nm, 10 nm, 15 nm, 20 nm, 30 nm, 40 nm or 45 nm. If the two-dimensional metal hydroxide comprises nickel-iron layered hydroxide nanosheets, the two-dimensional metal hydroxide has a thickness of 3-10 nm, a length of 20-200 nm, and a width of 20-200 nm; If the two-dimensional metal hydroxide comprises sheet-like nano-aluminum hydroxide, the thickness of the two-dimensional metal hydroxide is 3~10 nm.

7. The preparation method according to claim 3, wherein, Each component in the slurry satisfies one or more of the following conditions: The mass ratio of the carbon source to the two-dimensional template agent is 10:0.1, 10:0.2, 10:0.5, 10:1, 10:1.5, or 10:2; The mass ratio of the carbon source to the nanocellulose is 10:0.2, 10:0.5, 10:0.8, 10:1, 10:1.5, or 10:2; The mass ratio of the carbon source to the metal salt crosslinking agent is 10:0.02, 10:0.05, 10:0.1, 10:0.15, 10:0.2, 10:0.5 or 10:0.

8.

8. The preparation method according to claim 3, wherein, The slurry meets one or more of the following conditions: The solvent in the slurry is at least one of deionized water, ethanol, and N,N-dimethylformamide; The solid-liquid ratio in the slurry is (0.1~5):1; The slurry also includes a dispersant.

9. The preparation method according to claim 8, wherein, In the slurry, the mass ratio of the carbon source to the dispersant is 10:(0.1~2); or, In the slurry, the mass ratio of the carbon source to the dispersant is 10:0.2, 10:0.3, 10:0.5, or 10:

1.

10. The preparation method according to claim 3, wherein, The gradient calcination includes a first stage of calcination and a second stage of calcination; wherein the temperature of the second stage of calcination is higher than the temperature of the first stage of calcination; and / or, The washing process also includes sieving the porous carbon material.

11. The preparation method according to claim 10, wherein, The gradient calcination satisfies one or more of the following conditions: The calcination temperature of the first stage is 200~400℃; The first stage of calcination takes 1-8 hours; The calcination temperature in the second stage is 450~900℃; The second calcination period is 3 to 24 hours.

12. The preparation method according to claim 11, wherein, The gradient calcination satisfies one or more of the following conditions: The calcination temperature of the first stage is 250℃, 300℃, 350℃ or 380℃; The calcination time for the first stage is 2 hours, 4 hours, 6 hours, or 7 hours; The calcination temperature of the second stage is 500℃, 600℃, 650℃, 700℃ or 800℃; The second calcination time is 4h, 6h, 8h or 12h.

13. A method for preparing a silicon-carbon composite material, comprising: The porous carbon material as described in claim 1 or 2, or the porous carbon material prepared by the preparation method as described in any one of claims 3 to 12, is subjected to silane vapor deposition to obtain a silicon-carbon composite material.

14. A silicon-carbon composite material prepared by the preparation method as described in claim 13.

15. A battery comprising an electrode material, said electrode material comprising at least one of the porous carbon material as described in claim 1 or 2, or a porous carbon material prepared by the preparation method as described in any one of claims 3 to 12, or a silicon-carbon composite material as described in claim 14.

Citation Information

Patent Citations

  • Preparation method of porous carbon material and application of porous carbon material as electrode material

    CN103979529A

  • Method for preparing high-strength nanometre reticular fibrous membrane

    CN105932205A